SHWASAHARA DASHEMANI – AYURVEDA CLASSICAL SHAMANA YOGA FOR MANAGEMENT OF TAMAKA SHWASA (BRONCHIAL ASTHMA) - Patel Neha R.; Rajagopala S.; Patel KS; Kori VK (International Journal of Applied Ayurved Research, 2016)
Tamaka Shwasa is one among the five types of Shwasa Roga explained in Ayurveda classic. Tamaka Shwasa shows close similarity with bronchial asthma. There are abundant preparations explained in Ayurveda for the treatment of Shwasa Roga. Acharya Charaka has classified the drugs into group of ten popularly known as Mahakashaya or Dashemani, according to therapeutic action on system and diseases. Shwasahara Dashemani is one among them and used for the treatment of Tamaka Shwasa. Treatment of Tamaka Shwasa is classified as Shodhana (purification) and Shamana (palliative). Shwasahara Dashemani is one of the best Shamana therapies for Tamaka Shwasa. All the drugs of Shwasahara Dashemani are reported for anti-inflammatory action of Shathi and Tulasi, expectorant action of Shathi, Pooshkarmoola and Hingu, mast cell stabilizing and antihistaminic property of Shathi, Pooshkarmoola and Jivanti. Antiasthmatic properties of Shathi, Pooshkarmoola, Ela and Agaru and antimicrobial property of Shathi, Pooshkarmoola, Ela and Jivanti also have been proven. All these drugs are Agni Dipana, Vatanulomana, Kaphahara and Rasayana property and therefore are good palliative treatment for Tamaka Shwasa. In addition these drugs are easily available and cost effective too. Nowadays increasing prevalence of asthma in all age groups with lacuna in long term management of asthma; in such a scenario Shwasahara Dashemani as palliative treatment looks very promising.